2021
DOI: 10.1007/s42943-021-00031-x
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of the Operational Performance and Profitability of the U.S. Airlines

Abstract: Since 2008, a series of mega-mergers has dramatically changed the U.S. airline industry. Despite the presence of fewer airlines in the market, the competition remains intense, which forces airlines to continually search for ways to increase their efficiency to maintain survival and financial sustainability. To evaluate airline performance and disentangle the causes of inefficiency, this paper applied a two-stage network data envelopment analysis approach and a truncated regression to investigate the performanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 55 publications
1
3
0
Order By: Relevance
“…And among low-cost carriers, ultra-low-cost ones performed the best. This outcome supports the findings of Huang et al (2021) that “low-cost carriers are better off when the demands are volatile”. This also confirms that network carriers' economic sustainability is more at risk compared to low-cost carriers.…”
Section: Conclusion Limitations and Future Researchsupporting
confidence: 88%
See 1 more Smart Citation
“…And among low-cost carriers, ultra-low-cost ones performed the best. This outcome supports the findings of Huang et al (2021) that “low-cost carriers are better off when the demands are volatile”. This also confirms that network carriers' economic sustainability is more at risk compared to low-cost carriers.…”
Section: Conclusion Limitations and Future Researchsupporting
confidence: 88%
“…On the other hand, we observe a more consistent shift in reduction rate among network carriers in each quarter of 2020. Southwest Airways, one of the four largest carriers, “owning more than 80% of the market share combined” ( Huang, Hsu, & Collar, 2021 ), has the lowest reduction rate compared to its biggest rivals (American, Delta and United). This carrier benefits from both leisure and business customers while its competitors mostly depend on business travel and long-haul international flying.…”
Section: Resultsmentioning
confidence: 99%
“…different business models have become evident only during the crisis, as in the years before the COVID-19, a steady growth in demand allowed all air carriers to receive profit and hold a normal degree of financial stability. A similar study of the financial performance of the U.S. airlines conducted for the period before the COVID-19 pandemic (2015-2019) also concluded that airlines that follow the low-cost business model show higher efficiency not only financially, but operationally as well [14].…”
Section: Discussionmentioning
confidence: 88%
“…Finally, the aftermath of mega-mergers from 2008 to 2013 within the US airline industry was evaluated by Huang et al (2021). Their findings suggested that the number of employees negatively impacted airline operating efficiency, implying that staff reductions could adversely affect airline operations.…”
Section: Background and Literature Reviewmentioning
confidence: 99%